Evaluation of left ventricular function in patients with acute ischaemic stroke using cine cardiovascular magnetic resonance imaging. (15th July 2020) - Hellwig, Simon; Grittner, Ulrike; Elgeti, Matthias; Wyschkon, Sebastian; Nagel, Sebastian N.; Fiebach, Jochen B.; Krause, Thomas; Herm, Juliane; Scheitz, Jan F.; Endres, Matthias; Nolte, Christian H.; Haeusler, Karl Georg; et al.
Abstract: Aims: Heart failure (HF) is frequent in patients with acute ischaemic stroke (AIS) and associated with higher morbidity and mortality. Assessment of cardiac function in AIS patients using cardiovascular MRI (CMR) may help to detect HF. We report the rate of systolic and diastolic dysfunction in a cohort of patients with AIS using CMR and compare cine real‐time (CRT) sequences with the reference of segmented cine steady‐state free precession sequences. Methods and results: Patients with AIS without known atrial fibrillation were prospectively enrolled in the HEart and BRain Interfaces in Acute Ischemic Stroke (HEBRAS) study (NCT 02142413) and underwent CMR at 3 Tesla within 7 days after AIS. Validity of CRT sequences was determined in 50 patients. A total of 229 patients were included in the analysis (mean age 66 years; 35% women; HF 2%). Evaluation of cardiac function was successful in 172 (75%) patients. Median time from stroke onset to CMR was 82 h (interquartile range 56–111) and 54 h (interquartile range 31–78) from cerebral MRI to CMR. Systolic dysfunction was observed in 43 (25%) and diastolic dysfunction in 102 (59%) patients. Diagnostic yield was similar using CRT or segmented cine imaging (no significant difference in left ventricular ejection fraction, myocardial mass, time to peak filling rate, and peak filling rate ratio E/A). Intraobserver and interobserver agreement was high (κ = 0.78–1.0 for all modalities). Conclusions: Cardiovascular MRI at 3 Tesla is an appropriate method for the evaluation of cardiac function in a selected cohort of patients with AIS. Systolic and diastolic dysfunction is frequent in these patients. CRT imaging allows reliable assessment of systolic and diastolic function.